Fully automated measurement of aortic root anatomy using Philips HeartNavigator computed tomography software: fast, accurate, or both? - Kočka, Viktor; Bártová, Lucie; Valošková, Naďa; Laboš, Marek; Weichet, Jiří; Neuberg, Marek; Toušek, And Petr (European heart journal supplements, 2022)
Cardiac computed tomography (CT) is vital for safety and efficacy of transcatheter aortic valve implantation (TAVI). We aimed to determine the accuracy of fully automated CT analysis of aortic root anatomy before TAVI by Philips HeartNavigator software. This prospective, academic, single-centre study enrolled 128 consecutive patients with native aortic valve stenosis considered for TAVI. Automated HeartNavigator software was compared to the standard manual CT analysis by experienced operators using FluoroCT software. The sizing of the aortic annulus by perimeter and area significantly differed between both methods: mean perimeter was 76.43 mm vs. 77.52 mm (P < 0.0001) using manual FluoroCT vs. automated HeartNavigator software; mean area was 465 mm2 vs. 476 mm2 (P < 0.0001). Interindividual variability testing revealed mean differences between the two operators were 1.21 mm for the aortic annulus perimeter and 9 mm2 for the aortic annulus area. The hypothetical self-expandable transcatheter prosthesis sizing resulted in 80% agreement in 80% of cases. The time required to perform the automated CT analysis was significantly shorter than the time required for manual analysis (mean 17.8 min vs. 2.1 min, P < 0.0001). Philips HeartNavigator fully automated software for pre-TAVI CT analysis is a promising technology. Differences detected in aortic annulus dimensions are small and similar to the variability of manual CT analysis. Automated prediction of optimal fluoroscopic viewing angles is accurate. Correct transcatheter prosthesis sizing requires clinical oversight.
Keywords: Computed tomography; Transcatheter aortic valve implantation; Aortic valve